Perancangan Sistem Pendukung Keputusan Guru Berprestasi Berbasis Web Dengan Metode SAW - Santi Yuniarti; Jajat Sudrajat; Marjito Marjito (LPPM STMIK Mardira Indonesia, 2022)
School is an educational institution that is formal, non-formal, and informal with the aim of providing teaching, management and education to students carried out and given by teachers. Every teacher is entitled to an award for the performance, assignments, and work achievements that have been achieved. Through this award, it is hoped that every teacher can be motivated to become even better. Sometimes in the assessment process there are still inconsistencies, as well as difficulties in determining and finding out who the candidates can be who can be elected as teachers who excel because the decision on who can be elected as the best teacher still uses subjective criteria. To be able to avoid subjective assessments and obtain results that are in accordance with what is expected so that no party is harmed, a decision support system is needed for the selection of the best teachers with the SAW (Simple Additeve Weight) method. several criteria and weights that have been determined. At SDN Sukamenak 09 there is no system that supports the selection of the best teachers, the selection is still done manually. The selection of students is still considered subjective, the teacher still chooses the best students not based on predetermined criteria. It is hoped that this system can facilitate the teacher assessment process so that teacher assessment can be effective and efficient.